Penerapan Teknologi Pengolahan Limbah Tulang Ikan Tuna pada Kelompok Poklahsar Bubulla di Kelurahan Jambula, Kota Ternate - Tri Laela Wulandari; Adriani; Siti Nurjannah; Disnawati; Muh Aksa Azis (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
Fish processing activities in coastal communities often leave by-products that are not optimally utilized, including tuna bone waste. In Poklahsar Bubulla, Jambula Village, Ternate City, tuna bones generated from shredded tuna production were previously discarded, despite their potential as raw materials for value-added food products. This community service program aimed to strengthen partners’ production capacity through the application of appropriate processing technology and practical assistance in transforming tuna bone waste into marketable products. The program was implemented using a participatory approach through technical training, technology introduction, product processing practice, packaging assistance, and evaluation. The technologies introduced included a food dehydrator, flour milling machine, and vacuum sealer. The activities resulted in improved partner skills in processing tuna bone waste into fish bone flour and fish balls, better understanding of hygienic packaging practices, and stronger readiness to develop a small-scale business based on fishery by-products. Evaluation using pre-test and post-test among 11 participants showed an increase in the average score from 50.00 to 90.50, with an N-Gain value of 0.81 or 81%, categorized as high. The program also contributed to waste reduction and supported the creation of more efficient and sustainable fish processing practices at the community level. The findings indicate that appropriate technology adoption combined with community mentoring can enhance product diversification, increase the utilization of fishery waste, and support local economic empowerment. Keywords: technology; tuna bone waste; product diversification; community empowerment